2013
DOI: 10.1128/cvi.00148-13
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of a DNA Vaccine Encoding Apa Coencapsulated with 6,6′-Trehalose Dimycolate in Microspheres Confers Long-Term Protection against Tuberculosis in Mycobacterium bovis BCG-Primed Mice

Abstract: e Mycobacterium bovis BCG prime DNA (Mycobacterium tuberculosis genes)-booster vaccinations have been shown to induce greater protection against tuberculosis (TB) than BCG alone. This heterologous prime-boost strategy is perhaps the most realistic vaccination for the future of TB infection control, especially in countries where TB is endemic. Moreover, a prime-boost regimen using biodegradable microspheres seems to be a promising immunization to stimulate a long-lasting immune response. The alanine proline ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It remains to be seen whether nApa-boost during the expansion-phase, when higher BCG-load persists in the draining LNs and spleen 8 27 abolishes BCG-induced protection. However, no loss or improvement in BCG-induced protection was reported following microparticle-encapsulated apa genetic-boost during the expansion phase in a short-term protection experiment, and in fact, apa -boost modestly improved protection in the lung against chronic Mtb infection and prevented pathology 54 . In our study, subunit nApa-boost generated a strong booster effect despite targeting the same draining LNs where BCG persists 27 .…”
Section: Discussionmentioning
confidence: 87%
“…It remains to be seen whether nApa-boost during the expansion-phase, when higher BCG-load persists in the draining LNs and spleen 8 27 abolishes BCG-induced protection. However, no loss or improvement in BCG-induced protection was reported following microparticle-encapsulated apa genetic-boost during the expansion phase in a short-term protection experiment, and in fact, apa -boost modestly improved protection in the lung against chronic Mtb infection and prevented pathology 54 . In our study, subunit nApa-boost generated a strong booster effect despite targeting the same draining LNs where BCG persists 27 .…”
Section: Discussionmentioning
confidence: 87%
“…With these nucleic-acid based vaccines, how the genetic material is introduced into the host is an important factor for consideration. While free DNA is able to transfect cells and methodologies have been devised to facilitate its uptake without a vector [72], it has been shown that vector-delivered DNA vaccines have a higher efficacy [73]. Introducing foreign free DNA to the host without any protective coating vector raises the potential for an improper immune response.…”
Section: Using Liposomes To Deliver Nucleic Acid-based Vaccinesmentioning
confidence: 99%
“…Alanine is a major substrate for the hepatic synthesis of glucose, a significant energy substrate for leucocytes (Wannemacher et al, 1980). Alanine is also an important component of the glycoprotein (Carletti et al, 2013;El-Sabagh et al, 2014). Tyrosine, a product of phenylalanine degradation, is the immediate precursor for the synthesis of catecholamine hormones, indicating that an increased SNS activity and an up-regulation of catecholamine metabolism followed.…”
Section: The Effect Of Ee On Systemic Metabolitesmentioning
confidence: 99%